Análisis comparativo de las tecnologías NAS y san para la implementación en una empresa de Social Media Management. - Santillán Junco, Anthony Ariel (2024)
The case study focuses on performing a comparative analysis between Network Attached Storage (NAS) and Storage Area Network (SAN) technologies with the objective of determining which would be most suitable for implementation in a Social Media Company. Management. The strengths and weaknesses of both technologies will be examined in terms of performance, scalability, security and costs, with the aim of providing solid recommendations for the selection and implementation of the most appropriate solution.